Causes and predictors of unplanned reoperations within 30 days post laparoscopic pancreaticoduodenectomy: a comprehensive analysis - Zhang, Shiwei; Yadav, Dipesh Kumar; Wang, Gaoqing; Jiang, Yin; Zhang, Jie; Yadav, Rajesh Kumar; Singh, Alina; Gao, Guo; Chen, Junyu; Mao, Yefan; Wang, Chengwei; Meng, Yudi; et al. (Frontiers in Oncology, 2024)
To delineate the risk factors and causes of unplanned reoperations within 30 days following laparoscopic pancreaticoduodenectomy (LPD).A retrospective study reviewed 311 LPD patients at Ningbo Medical Center Li Huili Hospital from 2017 to 2024. Demographic and clinical parameters were analyzed using univariate and multivariate analyses, with P < 0.05 indicating statistical significance.Out of 311 patients, 23 (7.4%) required unplanned reoperations within 30 days post-LPD, primarily due to postoperative bleeding (82.6%). Other causes included anastomotic leakage, abdominal infection, and afferent loop obstruction. The reoperation intervals varied, with the majority occurring within 0 to 14 days post-surgery. Univariate analysis identified significant risk factors: diabetes, liver cirrhosis, elevated CRP on POD-3 and POD-7, pre-operative serum prealbumin < 0.15 g/L, prolonged operation time, intraoperative bleeding > 120 ml, vascular reconstruction, soft pancreatic texture, and a main pancreatic duct diameter ≤3 mm (all P < 0.05). Multivariate analysis confirmed independent risk factors: pre-operative serum prealbumin < 0.15 g/L (OR = 3.519, 95% CI 1.167-10.613), CRP on POD-7 (OR = 1.013, 95% CI 1.001-1.026), vascular reconstruction (OR = 9.897, 95% CI 2.405-40.733), soft pancreatic texture (OR = 5.243, 95% CI 1.628-16.885), and a main pancreatic duct diameter ≤3 mm (OR = 3.462, 95% CI 1.049-11.423), all associated with unplanned reoperation within 30 days post-LPD (all P < 0.05).Postoperative bleeding is the primary cause of unplanned reoperations after LPD. Independent risk factors, confirmed by multivariate analysis, include low pre-operative serum prealbumin, elevated CRP on POD-7, vascular reconstruction, soft pancreatic texture, and a main pancreatic duct diameter of ≤3 mm.Comprehensive peri-operative management focusing on these risk factors can reduce the likelihood of unplanned reoperations and improve patient outcomes.